2015
DOI: 10.1007/s11886-015-0659-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Lowering Drug Therapy for CVD Prevention: Looking into the Future

Abstract: Over the past three decades, statins have become first-line treatment for reducing LDL cholesterol (LDL-C) and cardiovascular disease (CVD). They have provided a clear, robust, and reproducible relationship between the absolute LDL-C reduction and the decrease in CVD; every 1 mmol/L (~40 mg/dL) in LDL-C reduction results in a 22 % decrease in CVD events. This relationship has recently been extended to reduction in LDL-C with a non-statin, ezetimibe, on top of statin therapy, further consolidating LDL-C as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…LDLC lowering and tolerability of EVO in the current study was congruent with evaluation of patients with statin intolerance in GAUSS-3, where EVO was well-tolerated and effective [1]. PCSK9 inhibitors now offer the promise of optimizing LDLC in the majority of patients with HeFH, CVD, and concurrent statin intolerance as previously published [25, 3739], and as in the high risk HeFH-CVD patients of current report, 67% of whom could not take any statin at any dose or sequence.…”
Section: Discussionsupporting
confidence: 79%
“…LDLC lowering and tolerability of EVO in the current study was congruent with evaluation of patients with statin intolerance in GAUSS-3, where EVO was well-tolerated and effective [1]. PCSK9 inhibitors now offer the promise of optimizing LDLC in the majority of patients with HeFH, CVD, and concurrent statin intolerance as previously published [25, 3739], and as in the high risk HeFH-CVD patients of current report, 67% of whom could not take any statin at any dose or sequence.…”
Section: Discussionsupporting
confidence: 79%
“…However, congruent with our open label, post commercialization study, as demonstrated by the controlled clinical trial, GAUSS-3, in patients with statin intolerance, EVO was well-tolerated and effective [8]. PCSK9 inhibitors now offer the promise of optimizing LDLC in most patients with HeFH, CVD, and concurrent statin intolerance [912, 3032]. …”
Section: Discussionmentioning
confidence: 75%
“…[ 30 ] Intensive statins therapy is important in stabilizing plaque, inhibiting plaque progression, and even preventing plaque rupture and occurrence of atherosclerotic events. [ 31 ] A large number of clinical trials have shown that statins can reduce 20%–40% of TC, reduce 20%–60% of LDL and reduce 7%–30% of TG. [ 32 ] Results of the SAMMPRIS study also suggest that the use of intensive statins therapy to decrease LDL-C to 1.8 mmol/L is beneficial in reducing atherosclerotic events.…”
Section: Discussionmentioning
confidence: 99%